THE STATE OF SPECIAL LIBRARIES IN DELTA STATE LOCAL GOVERNMENT COUNCILS: AVAILABILITY AND UTILIZATION PATTERNS - Okeke , Ifeoma Chukwuka (Ayden International Journal of Law, Political Science, and Administration, 2024)
The study investigated the availability and utilization of special libraries in local government area councils of Delta State Nigeria. The descriptive survey research was adopted as the design of the study with a total population of two hundred and ten (210) respondents who made up the staff of the information unit of the local government areas. 15 local government area councils were studied out of 25 local government area. A self-designed questionnaire was used to elicit information from the respondents. Data were analyzed using the mean score and the hypothesis was tested using the chi-square at 0.05 significant level. The study showed that there was no functional special library in all the local government area council but a corner in the information unit and the available information not well utilized. It was recommended above all that the local government area chairman should fund their libraries adequately and provide a functional library for the local government area councils.